The impact of consumed coffee on the digestive system - review of the latest research - Taborska, Nina; Martyka, Anna; Kubicka Figiel, Martyna; Ujma, Przemysław (Journal of Education, Health and Sport, 2024)
Introduction Coffee stands as the second most widely consumed beverage globally, following water.[1] Recent research on the effects of coffee consumption underscores its positive outcomes when adhering to recommended doses—typically ranging from 2 to 5 cups a day, amounting to a maximum of 400 mg of caffeine daily. This newfound perspective highlights the potential benefits of moderate coffee intake on our overall health and well-being. Aim of the study The objective of this study was to comprehensively review the existing knowledge regarding the impact of coffee consumption on diverse aspects of the gastrointestinal tract. Materials and methodology A literature review was conducted utilizing the PubMed, Google Scholar, and Google databases. Articles were systematically searched in both English and Polish, employing the keywords: coffee, caffeine, digestive system, digestion, and cancer. Results Recent research highlights coffee's diverse benefits, aiding digestion, hastening transit, and showing potential in cancer prevention. It stimulates gastric acid, enhances bile and pancreatic secretion, reduces gallstone risk, promotes large intestine movement, and modulates intestinal flora. Importantly, coffee isn't a primary factor in conditions like reflux, ulcers, inflammatory bowel diseases, or cancer. Conclusions Further research is essential to deepen our understanding of coffee's impact on the digestive system and its systemic effects on the body. Additionally, promoting awareness of safe daily caffeine doses that can contribute to health is worthwhile.